Knowledge, Attitude and Level of Involvement of Married Males in Family Planning - Bag, N. I.; Sahu, M.; Paul, B.; Das, R.; Bandyopadhyay, L.; Bhattacharyya, M.; Maitya, S. (Kathmandu University Medical Journal, 2022)
Background There is an age-old notion that family planning is women’s responsibility disregarding the fact that men have equal responsibility in fertility regulation. Although male involvement is getting more recognition, studies on men’s role in family planning are very few in the number in this part of the world. Objective To assess the knowledge, attitude and level of male involvement in family planning and to find out the factors associated with male involvement by contraceptive usage. Method A community based cross-sectional study was done from May to July 2021 among 165 currently married male, who had at least one child, living in Singur district of West Bengal. Cluster sampling method was done to select study participants and data were collected by pre-designed pretested questionnaire. Descriptive statistics, multivariable logistic regression was applied and data were analysed applying SPSS software. Result Only 36.4% participants were directly involved in family planning either by using condom or by withdrawal method but 65.5% participants were indirectly involved in family planning through spousal communication either by approving contraceptive use to their spouse or by decision making regarding family planning. Moreover, barrier of contraceptives usage were side effect (27%) and fear of impotence (25.5%). Male involvement was significantly associated with participant’s education [AOR (95% CI= 3.63 (1.45-9.05)], caste [AOR (95% CI= 7.06 (2.55-19.51)], number of living children [AOR (95%CI= 5.01(1.95-12.87)], desire for more child [AOR (95% CI=0.34 (.13-.87)] and attitude on family planning [AOR (95% CI= 3.55 (1.41-8.94)]. Conclusion This study identified the prevailing gender norms in rural areas. Advocacy for male involvement in family planning by health personnel during counselling of eligible couples should help in increasing contraceptive coverage in the long run.